(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Polycystic Ovarian Syndrome is a heterogeneous disorder. It is the most common endocrinopathy in women and the most common cause of anovulatory infertility. Hyperandrogenism is a salient feature of PCOS. At present, Hormone therapy and chemical drugs are recommended for the treatment of hyperandrogenism in PCOS and this treatment has several adverse side effects. Hence Traditional medicine remedies have become an emerging trend among people without any side effects. In traditional and modern medicine, Clitoria ternatea is focused on as an enhancer of reproductive health. The present study was undertaken to develop a Nutraceutical product - capsule filled with powdered dry Clitoria ternatea flower for the treatment of PCOS. The formulated Nutraceutical product (capsule) was rich in minerals and total flavonoids. It contained 93.4% of moisture, 6% of total ash, 445.8 mg/100 g of calcium, 811.2 mg/100 g of potassium, 143.5 mg/100 g of magnesium, and 102 mg QE/g of total flavonoids. The binding affinity of flavonoids such as Quercetin, Kaempferol, and Myricetin as present in the petals of Clitoria ternatea were explored with the protein CYP 17-cytochrome P450 which is responsible for hyperandrogenism due to its overexpression and leads to PCOS. The binding affinity of Ketoconazole, Spironolactone, and Flutamide (which are all used as drugs for treating hyperandrogenism) were also explored with the protein CYP 17-cytochrome P450 to compare the efficiency of flavonoids in the treatment of PCOS.